Shapes and Their Equations: Experimentation with Desmos - Iobst, Christopher Simon (Ohio Journal of School Mathematics, 2018)
The author explores common polygons---squares, triangles, trapezoids---and uses the free online grapher, Desmos, to derive single equations that generate the shapes. Throughout, the author discribes his inquiry-based approaches---the trials and errors he employs in his eventual discovery of various shape-generating equations.